2020
DOI: 10.1002/ijc.32850
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term risk of colorectal cancer after screen‐detected adenoma: Experiences from a Danish gFOBT‐positive screening cohort

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
(33 reference statements)
0
13
0
Order By: Relevance
“…The initial literature search resulted in 1634 studies. After the selection criteria were applied, 112 studies were selected and reviewed in detail, and 12 studies were included in the final analysis 10,11,[17][18][19][22][23][24][25][26][27][28] (Figure 1). Four studies were from the United States (n ¼199,145), 1 was a multicenter study from Taiwan and China (n ¼ 4483), and 1 study each was from Korea (n ¼ 2452), Israel (n ¼ 728), the United Kingdom (n ¼19,806), France (n ¼5,779), Norway (n¼40,826), Denmark (n ¼ 711), and Poland (n ¼236,089).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The initial literature search resulted in 1634 studies. After the selection criteria were applied, 112 studies were selected and reviewed in detail, and 12 studies were included in the final analysis 10,11,[17][18][19][22][23][24][25][26][27][28] (Figure 1). Four studies were from the United States (n ¼199,145), 1 was a multicenter study from Taiwan and China (n ¼ 4483), and 1 study each was from Korea (n ¼ 2452), Israel (n ¼ 728), the United Kingdom (n ¼19,806), France (n ¼5,779), Norway (n¼40,826), Denmark (n ¼ 711), and Poland (n ¼236,089).…”
Section: Resultsmentioning
confidence: 99%
“…All of these studies were population-based cohort studies, of which 4 were prospective, 22,23,25,26 and 7 were multicenter studies. 11,[17][18][19][26][27][28] Only 2 studies 24,25 reported the actual number of colonoscopies performed in each group for the duration of follow-up. An overview of the individual studies with their demographic data is provided in Table 1 and Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations